Strategi Kolaborasi dalam Pengembangan dan Keberlanjutan Pasar Tematik Wisata Jelajah Danau Ranau Lumbok Seminung Kabupaten Lampung Barat - Nurliana, Nurliana (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The West Lampung Regency Government has allocated IDR 70 billion for the development of the Lake Ranau Lumbok Seminung Thematic Tourism Market as part of its tourism-based economic development strategy. This market is designed around the concepts of tourism, culture, and shopping to attract visitors and enhance the welfare of local communities. However, the primary challenge lies in ensuring the market's sustainability and effective utilization so that it does not experience the same fate as previous tourism facilities in the area, which suffered from suboptimal usage and sustainability. This policy paper employs a qualitative descriptive approach, utilizing Focus Group Discussions (FGDs), field studies, and policy analysis. The study’s findings indicate that the development and sustainability of the market require robust regulations, cross-sector collaboration, and community empowerment. Therefore, it is recommended that a Regent Regulation be enacted to systematically manage thematic markets, integrate a tourism curriculum into local education, and prioritize the designation of market locations in community and MSME empowerment programs. The implementation of this policy is expected to support inclusive economic growth, enhance the attractiveness of regional tourism, and ensure the sustainability of thematic tourism markets as strategic assets for West Lampung Regency.